Muslim fashion dynamics: The mediating role of positive emotion in elucidating impulsive buying behavior - Adriyanto, Andhy Tri; Octavia, Ayu Nurafni; Romadon, Ahmad Sahri (Asian Management and Business Review, 2024)
Growing Muslim fashion trends drive diverse demands. Business must cater to varied preferences, offering a range of styles to suit consumer wishes in the expanding Muslim fashion industry. This study conducted in Semarang City, Central Java, Indonesia involved 150 respondents and employed SmartPLS to test the interplay of fashion involvement, positive emotion, and impulsive buying. Contrary to expectations, a direct link between fashion involvement and impulsive buying was not significant. However, positive emotions emerged as a crucial mediator, indicating that emotional experiences play a pivotal role in shaping impulsive buying behaviors, especially within Muslim fashion. This research contributes novel insights by uncovering the nuanced relationship between fashion involvement and impulsive buying, highlighting the significant mediating role of positive emotions. It enriches the broader understanding of consumer behavior in the context of the Muslim fashion industry, offering valuable psychological perspectives for consumer management. The absence of a significant direct effect prompts exploration into moderating variables, such as cultural and religious factors within the Muslim community. Concerns about self-reported data and response bias suggest avenues for further refinement in future studies. The study enriches existing theories by emphasizing the intricate interplay between fashion involvement, positive emotions, and impulsive buying.